Interactive E-learning environment for phase-locked loop in IC - Chen, Jasmine PeiSi (Nanyang Technological University, 2021)
In recent years, the advent of information and communication technology (ICT) drives the education system to strive for integrating ICT into the curriculum framework with the intent of undergirding self-directed learning and exploring interests outside traditional classroom settings.